Mental health and depression among school going adolescents: excerpts from a school based study of Nadia district, West Bengal - Basu, Gandhari; Biswas, Sujata (Asian Journal of Medical Sciences, 2017)
Background: Adolescence is the gateway to health promotion and marked as the transition period between childhood and adulthood. They suffer from various psychosocial problems at any point of their life. Depression during adolescence is considered as an important public health emergency. Aims and Objectives: To assess the presence of some mental health symptoms by Beck’s Depression Inventory (BDI) among school going adolescents and also to find out the prevalence of depression along with associated factors. Materials and Methods: A crosssectional, descriptive epidemiological study was conducted among adolescents of class VII to IX of an English medium school of Kalyani in Nadia district between July and August, 2016. Information on socio demographic variables along with responses on the questions related to various aspects of mental health was gathered by validated BDI and Global school health survey questionnaire. Depression was classified based on the scores obtained and a scale was used. Results: A total of 167adolescents were assessed, mean age of 13.63 years with more boys (110). Mental health analysis revealed nine attempted suicide cases. Nearly half of the pupil reported of punishment feelings (71) and self-criticism (68). The prevalence of overall depression was 34.2%, mild one topped the list. Level of depression was significantly more in higher age group, class VII and among those adolescents who did not stay with their parents (P<.01). Conclusion: The present study provides a composite scenario of mental health status and depression among adolescents. The findings reveal that depression is gradually increasing in respondents. This study also demonstrated the need for secondary prevention and raises deep concern. School based training programme and quarterly counselling under psychiatrist’s guidance in a holistic approach may manage the problem to a great extent. Asian Journal of Medical Sciences Vol.8(5) 2017 64-69